Dating the Peopling of Northwestern South America: An AMS Date from El Inga Site, Highland Ecuador. (2nd January 2016) - G. Nami, Hugo; Stanford, Dennis J.
Abstract : The El Inga site in Ecuador produced an important number of fishtail (or Fell) points. Early 1960s conventional radiocarbon assays yielded dates ranging between 9000 and 4900 14 C yr BP. Even the oldest one seems too young given dates for these artifacts in South America. We recently AMS dated a curated sample from Bell's original excavation. The new results are in agreement with dates obtained from fishtail point sites in the rest of the continent.